Arterial hypertension - definition, epidemiology, etiology, complications and treatment - Ilko, Agnieszka; Wudarczyk, Beata; Czyż, Rafał; Jankowska-Polańska, Beata (Journal of Education, Health and Sport, 2018)
Arterial hypertension is classified as a chronic disease. It belongs to the group of disease that increase the risk of occurrence of cardiovascular complications, which if left untreated can lead to sudden death. It is estimated that in Poland currently 32% of the population suffers from arterial hypertension. Despite great progress in the diagnosis and treatment of hypertension, it is still a huge medical-socio-economic problem. Increasing the emphasis on patient education can significantly affect self-control, adaptation to recommendations and, consequently, in the future perspective will reduce the mortality rate among patients with this disease. The aim of this work is to draw attention to the still present problems of patients with hypertension by presenting the currently valid definition, epidemiology, etiology of the disease, complications and methods of treatment.